Comparative analysis of left atrial volume and strain parameters in hemodialysis vs. peritoneal dialysis patients using four-dimensional automatic quantification technology - Mei Jin; Lingxiang Ma; Bing Li; Xuning Huang; Meihua Chen (Renal Failure)
Background Cardiovascular complications remain a leading cause of mortality in patients with end-stage kidney disease undergoing dialysis. This study aimed to evaluate differences in left atrial (LA) structure and function between hemodialysis and peritoneal dialysis patients using four-dimensional automatic left atrial quantification (4D Auto LAQ) technology.Methods This study included 125 patients with end-stage kidney disease, categorized into hemodialysis (n = 69) and peritoneal dialysis (n = 56) groups. Conventional echocardiography and 4D Auto LAQ were used to assess LA volume and strain parameters. Differences between groups were analyzed.Results Hemodialysis patients exhibited significantly larger LA minimum volume, maximum volume, pre-atrial contraction volume, and maximum volume index compared to peritoneal dialysis patients (p < 0.05). Conversely, hemodialysis patients had significantly lower LA reservoir circumferential strain (LASr-c) and conduit circumferential strain (LAScd-c) than peritoneal dialysis patients (p < 0.05). LA ejection fraction (LAEF) correlated positively with LASr-c (r = 0.809). Multivariate regression analysis identified LASr-c as independently associated with dialysis modality and LAEF. Sensitivity analysis confirmed LAEF as an independent determinant of LASr-c.Conclusions Hemodialysis is associated with increased LA volume and impaired LA function compared to peritoneal dialysis. These findings highlight the importance of LA monitoring in dialysis patients to identify early cardiac dysfunction.